Cursos de licenciatura em Pedagogia das Universidades Estaduais da Bahia: análise da formação matemática para a educação infantil - Brito, Mirian Ferreira de (2015)
Studies and research on early childhood education gained greater prominence in the past five decades, it was motivated by the Federal Constitution, which recognized this educational stage and included it as part of basic education. Such change ensured some rights to the children, but even with advances and documents about it, even as the Guidelines and Curriculum Framework, some gaps are still visible in teacher training at this stage of education. Thus, we seek answers for regarding questions to the courses and curriculum, where such teachers graduate, particularly in mathematics, for being part of our training universe, work and studies. Thus, we seek through this qualitative approach research, to analyze aspects of teacher training to mathematical knowledge in the curriculum structures of the Degrees in Education, of the Bahia State Universities, taking into account three components: theoretical concepts about of the mathematics, specific mathematical content and practical contents of the mathematics. Therefore, we analyzed the flow charts and summary of the curriculum components, presenting mathematical knowledge, as well as profissiográficos profiles of courses. As main results, we can see the flow charts, which from the eighteen presented courses, only three of them exhibited two curriculum components, and the others exhibited only one component. In the summary, we checked that ten components showed no specific contents of mathematics and only six offered the three components. At profissiográficos profiles, we checked that the teaching and management were nominated in all courses, since teaching for early childhood education, despite being recorded in twelve courses, it do not appear on any of them. In this way, the data disclosed in the general training and/or fast by the ampleness of indicated performances in the courses, and also confirmation of low workload for researched mathematical contents theoretical, specific and practical